Criminology - Jones, Stephen (Oxford University Press, 2001)
The third edition of Criminology offers updated and expanded coverage on the depth and diversity of criminological theories. Following a historical path through the development of criminological theories, and with full references to guide the reader to further, more in-depth, study of any particular aspect, this text will be an engaging read for all those studying the subject